CONCEPÇÕES DE ATORES SOCIAIS SOBRE EDUCAÇÃO NA RELAÇÃO COM POLÍTICAS DE SAÚDE - Ubessi, Liamara D.; Frantz, Walter; Falkembach, Elza M. F.; Righi, Liane B.; Stumm, Eniva M. F.; Pansera-De-Araújo, Maria C. (Salão do Conhecimento, 2013)
Resumo